Artificial Intelligence and Predictive Policing: Reconstructing Fair Trial Principles in the Age of Algorithmic Justice - Ahmad Nurun; Ismaya Dewi Priyani (Gemini Littera Publishing, 2026)
The rapid expansion of artificial intelligence (AI) within criminal justice systems has transformed contemporary law enforcement from reactive adjudication toward predictive governance based on algorithmic surveillance, risk assessment, and data-driven policing. While predictive policing technologies are frequently promoted as instruments of efficiency and objectivity, their increasing use has generated profound concerns regarding algorithmic bias, procedural inequality, opacity in decision-making, and the erosion of fair trial guarantees. This article examines how the rise of algorithmic justice challenges the foundational principles of modern criminal procedure, particularly the presumption of innocence, transparency, equality before the law, and the right to defense. Using normative legal research with conceptual and comparative approaches, this study analyzes the development of predictive policing and AI governance in several jurisdictions, including the United States, China, the European Union, and Indonesia. The article argues that conventional fair trial doctrines are increasingly inadequate in responding to opaque and predictive systems of algorithmic governance because existing procedural safeguards were primarily designed for human decision-makers rather than automated computational systems. This study further demonstrates that AI-driven law enforcement not only reproduces structural discrimination embedded within historical criminal data, but also expands state surveillance capacities through technologically mediated forms of governance. As a theoretical contribution, this article proposes a reconstruction of fair trial principles through a framework of human-centered algorithmic governance emphasizing algorithmic transparency, explainability rights, meaningful human oversight, anti-discrimination safeguards, independent algorithmic auditing, and digital procedural rights. Ultimately, the article argues that the future legitimacy of criminal justice systems depends upon the ability of legal institutions to control algorithmic power while preserving constitutionalism, procedural justice, and fundamental human rights in the era of digital governance.